Hiding Random text using Steganography - KOLAPO RIDWAN OLAYINKA (International Journal of Multidisciplinary Research and Studies, 2023)
The introduction of steganography has brought a lot of improvement to information security. Security issues is taken into account a significant concern which is why management systems offices still opt to follow the normal way of addressing record keeping. This study aims to ensure data security using Steganography. The method used in for the steganography technique in this study is the RGB techniques, as every pixel is considered to be a combination of RGB. The entire message to be hidden is split-ed into equal 2-bit values and embedded in the red pixel value of the image. This is passed until the end of the image. The message length is also embedded in the image by the software solution designed. The same software must be used to receive, decode the image, and extract the message. The result of this study is presented as a software solution and the images used for information hiding are not limited to any type of image as images from different sources and types can be used for hiding text, also the image used for steganography resulted in having higher dimension size as this compensates for the addition security level. In conclusion, the steganography system is aimed to protect the confidentiality of data and present it as an image as this will not easily attract security threats.